2012
DOI: 10.1177/014556131209100508
|View full text |Cite
|
Sign up to set email alerts
|

Active Olfactory Training for the treatment of Smelling Disorders

Abstract: Olfactory function appears to be influenced by repeated odor stimulation. We conducted a nonrandomized, nonblinded, retrospective study of the impact of an 8-month period of olfactory training in patients with olfactory dysfunction. Our study population was made up of 46 adults-14 men and 32 women (mean age: 59.17 ± 13.25 yr)-with olfactory dysfunction of different etiologies (sinonasal: n = 15; post-upper-respiratory-tract infection [URTI]: n = 16; post-traumatic: n = 7; and idiopathic: n = 8). All patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
75
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 15 publications
6
75
0
3
Order By: Relevance
“…We also found that odor identification (I score) significantly improved after OT in postinfectious patients. This is in line with previous reports suggesting that OT may induce changes in subjects' higher cognitive processes, leading to improved perception of suprathreshold odors . Therefore, our results support the two lines of research showing that OT might positively influence both cognitive processes involved in odor perception and neural processes responsible for odor detection …”
Section: Discussionsupporting
confidence: 93%
“…We also found that odor identification (I score) significantly improved after OT in postinfectious patients. This is in line with previous reports suggesting that OT may induce changes in subjects' higher cognitive processes, leading to improved perception of suprathreshold odors . Therefore, our results support the two lines of research showing that OT might positively influence both cognitive processes involved in odor perception and neural processes responsible for odor detection …”
Section: Discussionsupporting
confidence: 93%
“…However, the positive impact of OT is well‐established (Damm et al, ; Pekala et al, ; Sorokowska et al, ) and the control group in such studies have never demonstrated a significant increase in olfactory function as per the patient group (Sorokowska et al, ). Moreover, and the increase in TDI score in studies with similar patient groups has been of the same magnitude as per our patient group (e.g., 4.09 TDI increase; Fleiner, Lau, & Göktas, ) buttressing our conclusion that the enhancement in olfactory function is due to the odorant exposure.…”
Section: Discussionsupporting
confidence: 86%
“…Peroral caroverine, an N-methyl-D-aspartic acid (NMDA) receptor antagonist [88], as well as sodium citrate nasal spray [95] have been shown to be effective in placebo-controlled studies. In addition to drug treatments, acupuncture [96-99] and olfactory training [100,101] have also been investigated. It is likely that any successful treatment of smell loss would also improve the associated symptoms of distorted olfactory perception.…”
Section: Introductionmentioning
confidence: 99%